Conhecimento e piedade vital : um exercício hermenêutico para a pastoral escolar e universitária e os indicativos para uma teologia da educação - Artigas, Flávio Ricardo Hasten Reiter (2008)
An hermeneutic interpretative research in wesleyan heritage texts, with emphasis on the concept of "knowledge and vital piety", considering the practices of School and Universitary Pastoral Ministry, in the Methodist education instituition. This research is developed in three complementary moments. There is a John Wesley s historical and theological rescue in the first chapter, in his education emphasis. Followed by an analysis in the School and Universitary Pastoral Ministry regimental statements, it functions, with an interpretative reading crossing the wesleyan heritage, and daily practices of Pastoral on methodist education instituition. Also considering other main documents for education an methodism than "Diretrizes para a Educacao na Igreja Metodista", as "Plano para a Vida e Missao da Igreja Metodista" and "Credo Social". In the last chapter an interpretation combine wesleyan theological and historical tradition, and School and Universitary Pastoral Ministry function and practices, challenges, doubts and possibilities. Third chapter evaluate some indications toward a theology of education settling for further researches. In this history, theological and practice combined, conclusions build ideas to challenge knowledge construction to answer and be helpfull for Methodist Church Mission practices through it education instituition with wesleyan heritage, and Methodist educational efforts in the Mission perspective.